Penerapan Inovasi Pembelajaran Merdeka Belajar Pada Siswa SD dan SMP Dengan Metode Game Based Learning di Lembang Rantedada - Devianti Limbong; Grace Sriati Mengga; Yohanis Lotong Ta’dung (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
Community service activities were carried out in Lembang Rantedada, Mengkendek District, Tana Toraja Regency. The problems found in Lembang Rantedada, especially in Rantedollok Hamlet, namely in Lembang Rantedada there are no educational institutions such as elementary, junior high, and high school, Therefore, children in Lembang Rantedada look for schools that are close to their homes, so some of them do not know each other and children in Lembang Rantedada spend more of their time playing online games, thus affecting their interest in learning. The solution used to overcome the problem is to provide additional lessons to elementary and junior high school students through tutoring conducted 2 times a week in three hamlets. The learning used is the Lecture and Role Play method. The parties involved in the guidance are students. The results achieved from the tutoring are elementary and junior high school students in Lembang Rantedada can get additional learning outside of learning at school, increasing students' interest in learning where through Bimbel activities students are prepared to be independent in learning and also they can get to know each other